BSA /anti BSA Interaction Study using a Novel Modular Surface Plasmon Resonance (m-SPR) Device - Mohd Azwady Wan Ahamad, Wan; Kamarun, Dzaraini; Kamil Abd Rahman, Mohd (International Journal of Engineering and Technology, 2018)
A novel modular surface plasmon resonance (SPR) device fabricated in-house was tested for its function and linearity for biomolecular interaction using BSA and Î±-BSA as model biomolecules. The sensor surface was initially saturated with BSA molecules and their interactions with Î±-BSA molecules were then monitored over various concentrations of Î±-BSA. The newly developed modular SPR biosensor was able to detect biomolecular interactions between BSA and Î±-BSA at Î±-BSA with good linearity. Stabilization of the interactions was achieved within 10 minutes of monitoring time.Â